HPV vaccines to prevent cervical cancer and other HPV-associated diseases - Schiller, John (Henry Stewart Talks, 2018)
Human papillomavirus (HPV) lifecycle, Cervical HPV infection and progression to cancer, Primary and secondary prevention method, Prophylactic HPV vaccines, Efficacy and durability of HPV viral-like particles (VPL) vaccines, The potential of a one-dose vaccination program, Randomized trials, Vaccine protection against pre-malignant lesions, Vaccine safety record & effectiveness, HPV vaccine uptake, Antibody response, Increasing vaccine use